Effect of 16 week strength and endurance training on hip-knee coordination variability by vector coding techniques of Taekwondo side kick - Safaei, M. A.; Barnamehei, H. (19th International Symposium "Modern Science and Practice for Strength and Endurance Training" October 10-12, 2018, 2020)
Introduction: Yeop Chagi (Side kick) is a very powerful technique, in which the athletics simultaneously raises the knee and rotates the body 90 degrees, while extending their leg. There are two main factors that contribute to lower limb coordination: neurological functions and biomechanical constraints [1]. Therefore, the aims of the present study was analysis the effect of 16 week strength and endurance training on taekwondo Yeop Chagi (YC) kinematics coordination [2].